Polymorphism of goat DGAT1 gene and their association with milk production traits - Ozmen, Ozge; Kul, Selim (Indian Counc Agricultural Res, 2014)
The purpose of the study was to identify genotype frequencies of single nucleotide polymorphisms the intron 6, exon 7, intron 7, exon 8, intron 8 and exon 15, intron 15, exon 16, intron 16, exon 17 and partially 3' untranslated region (UTR) in goat DGAT1 gene and its possible association genotypes with milk traits in dairy goat breeds by means of PCR-RFLP assays. Goats 185: Saanen n: 35; Damascus n: 30; Halep n: 30; Maltase n: 30; Alpine n: 30; Kilis n: 30) were used for investigating. PCR products were digested separately with Eael, NlaIII and AIul restriction enzymes for exon 8, exon 16 and 17, respectively. No polymorphisms were detected at the Eael and AIul cleavage sites for exon 8 and exon 17 in sampled goat populations. However, biallelic polymorphism was found with restriction endonuclease in intron 16 of DGAT1 gene and two genotypes were detected and TC, in which IT was the predominant genotype and allele T was predominant allele in six goat breeds. No significant statistical results were founded in milk yield, fat, protein and lactose values with TT and TC genotypes were detected. We have described here for the first time an NlaIII PCR-RFLP method for detecting T-to-C mutation in intron 16 goat DGAT1 locus: CATG-to-CACG.
Keywords: DGAT1 gene; Polymorphism; Goat; Milk traits